A pequena frase "a esperança venceu o medo" na imprensa cotidiana brasileira : uma leitura discursiva - Souza, Marilena Inácio de (2012)
It is not from today that we live with the discursive spread of small phrases . Since immemorial times, phrases have been separated from their contexts or co-texts and given into circulation singly, as if they were statements above and outside the common texts be they literary, religious, political, scientific or philosophical. In our western society, the phenomenon always occurred, but maybe it has intensified the contemporary world. Media is perhaps the main vehicle and, therefore, the most efficient manager: headlines, eyes , phrases of the week, article titles, main calls, etc. Present trend is fragmentation, of short discourses, due to the fastness with which the facts are given into narrative. The small phrases is, in fact, a communicational practice that newspapers, sites, social networks manage when they publish statements in highlighted condition in their pages. Discursive proliferation of the statement Hope overcame fear taken, here, as analysis object is an example of what we are talking about. Its constant circulation through different fields leads us to interpret it as a pandemic statement, a kind of statement that exceeds even the limits of panaforization (a term that combines pan , of pandemic, and aphorization), occurrences of this statement exceeds the limits of time and space (they keep alive and moves at full speed in media enunciative detachments ten years after its eruption/media explosion in the speech of the elected candidate Luiz Inácio Lula da Silva-PT in 2002). It is, in this case of a statement which discursive status resemble that of a proverb that goes from media support to media support, lasting through times. Throughout thesis, anchored in the discussions proposed by Dominique Maingueneau (2006, 2007, 2010a, 2010b), we show that statement in study infiltrates in newspapers headlines, in article titles, in Youtube video titles, in main calls for forums and debates etc, making raise all species tensions in media. Without the attempt to define all the meanings that different occurrences of the statement Hope overcame fear circulates, because in each manifestation, the meanings are historicized of a different manner, this doctoral research assumes a dual task: in one hand, it tries to account particular data of a non-topic route unity, on the other hand, seeks to describe and analyze linguistic-discursive functioning of the constants detachments of the referred statement in the media Brazilian context. Recent works developed by Maingueneau, specially, those resulting of his research program Aphorizating enunciation that will be the theoretical and methodological support in this work. We believe that the calibration of the conceptual tools mentioned in distinct data frequented by Dominique Maingueneau can illuminate paths for the explanation and comprehension of the linguistic-discursive functioning, not only of the statement Hope overcame fear , but of a whole set of statements, whose main characteristics stems from the fact that they are quotable , memorable , detachable , not only for a brief period, but for a relatively long time with a unique ability of mean different events without cling to none. The analysis that we propose, from a very specific corpus can, thus, gives even more consistence to the Aphorizating Enunciation, which is really new in the franco-brazilian space. We believe that our research can also add to a interpretation of recent history of Brazilian politics. However, an interpretation that does not departs from huge happenings, but of the discursive production of historical events through small phrases .